Optimization of Amount of Ethylene Glycol and Reflux Temperature in Glycolysis of The Waste Polyethylene Polythene Terephthalate (PET) on Jerbung Shrimp in Padang City - Atikah Muthmainnah; Indang Dewata (Jurnal Periodic Jurusan Kimia UNP, 2020)
Polyethylene Terephthalate (PET) is one of the most widely used plastics, especially in packaging. The many uses of PET along with the increasing amount of PET waste that has negative impact on the environment because PET is a plastic that can only be used for one time use and cannot be decomposed naturally. Therefore, it is necessary to recycle PET by depolymerizing by glycolysis into bis (2-hydroxyethyl terephthalate) BHET. In this research, glycolysis was using EG variations of 20, 30, 40, and 50 mL and temperature variations of 166, 176, 186, and 196 oC. The results obtained 83.425% BHET yield under optimum conditions of EG as much as 30 mL and temperature of 196 oC. The results was characterized by Fourier Transform Infra Red type perkin elmer universal ATL Sampling Accessors 735 B at wave numbers 600 - 4000 cm-1 to determine the functional groups that make up the BHET.